Indonesian Foreign Policy: Strategy for Facing Rivalry United States Politics with China - Yusran, Yusran (Universitas Sultan Ageng Tirtayasa, 2025)
How many decades ago was the United States overwhelmingly influential in the Indo-Pacific region. Many policies prove that international relations are driven by the national interests of the United States in this region. However, throughout the years, the American domination of the region has started to weaken as a result of China’s fast and advanced development. Due to its Belt and Road Initiative policy, this country has long since become a superpower that could challenge American hegemony. The aim of this study is to review the foreign policy of Indonesia when facing the competition of the politics of the United States and China, and particularly in the Indo-Pacific region. The approach of this study was qualitative with a descriptive method, and the data was collected by observation and deep interviews with experts and diplomats at the Ministry of Foreign Affairs. Meanwhile, the researchers also found the studies by considering the literature. The findings of this research showed that Indonesia is consistent with operating on the free and active political principle abroad when facing the competition between the United States and China in the Indo-Pacific region. It also strategically operates multilaterally, balancing its bilateral relations, achieving economic independence and strengthening its defense, and prioritizing soft diplomacy. However, the strategic position also puts Indonesia on various challenges that risk neutralizing its position, being dragged into a proxy conflict, relying on an economic structure from China, and incurring the impact of South China Sea disputes on its national interests. Thus, adaptive policy and strengthening its overseas capabilities are essential to make Indonesia more robust and responsive to the dynamics of the competition between big powers.